Efektivitas Penerapan Sistem Presensi Online Dalam Menunjang Kedisiplinan Kerja Pegawai Di Kantor Sekretariat DPRD Sukoharjo - Solikhah, Solikhah; Pramono, Joko; Suranto, Joko (Solidaritas, 2024)
To improve employee discipline, efforts to control and supervise the discipline ofemployee working hours need to be carried out continuously and consistently. One of thefactors that can be used as a monitoring and control tool is to see the level of employeeattendance which is periodically evaluated. The manual attendance reporting system that hasbeen carried out tends to manipulate and does not submit employee attendance reports as theyare. In this study the authors used descriptive empirical research with a qualitative approach.This research was conducted at the Sukoharjo Regency DPRD Secretariat Office.The selection of the location as the place of this research was carried out deliberatelybecause the Sukoharjo DPRD Secretariat Office was one of the offices that implemented anonline attendance system in the internal arrangement carried out in the field of human resourcemanagement. Data collection techniques: observation, interviews, documentation. the resultsshowed that the implementation of online attendance at the Sukoharjo DPRD Secretariat Officewas running quite well. Judging from Tangkilisan's indicators: Target achievement, wellrealized in improving work discipline. Adaptability, at the beginning of its application therewere few obstacles in using it, but employees were able to adapt so that they could use onlineattendance well. Job satisfaction, when the online attendance system is implemented, employeediscipline has increased, because it is supported by the Income Supplement Allowance (TPP)if attendance and work are optimal. Responsibility, employees at the Sukoharjo DPRDSecretariat Office are expected to increase the discipline of their attendance and performance,so that they can be competitive at work. So that with the nature of discipline to improve workperformance will be maintained.Keywords: Effectiveness, Discipline, Online Presence